Microfluidics-Enabled Multi-Material Maskless Stereolithographic Bioprinting - Miri, Amir K. (Adv Mater, 2018)
This communication presents a stereolithography-based bioprinting platform for multi-material fabrication of heterogeneous hydrogel constructs. Dynamic patterning by a digital micro-mirror device (DMD), synchronized by a moving stage and a microfluidic device containing four on/off pneumatic valves, is used to create 3D constructs. The novel microfluidic device is capable of fast switching between different (cell-loaded) hydrogel bioinks, to achieve layer-by-layer multi-material bioprinting. Compared to conventional stereolithography-based bioprinters, our system provides the unique advantage of multi-material fabrication capability at high spatial resolution. To demonstrate the multi-material capacity of our system, a variety of hydrogel constructs are generated, including poly(ethylene glycol) diacrylate (PEGDA) and gelatin methacryloyl (GelMA). The biocompatibility of our system is validated by introducing cell-laden GelMA into the microfluidic device and fabricating cellularized constructs. A pattern of PEGDA frame and three different concentrations of GelMA, loaded with vascular endothelial growth factor, is further assessed for its neovascularization potential in a rat model. The proposed system provides a robust platform for bioprinting of high-fidelity microstructures on demand for applications in tissue engineering, regenerative medicine, and biosensing, which are otherwise not readily achievable at high speed with conventional stereolithographic biofabrication platforms.